(untitled) (Islas, 2025)
Introduction: This study analyzes the representation of work in the phraseology of the Spanish language. It departs from the scarcity of systematic research on work-related phraseology and its variation, as well as from the need to understand how these expressions encode sociocultural values and ideologies. Methods: The sample of 113 phraseological units was obtained through filtering the database of the Phraseology and Multilingual Translation Research Group at the University of Alicante. A phraseological and exploratory approach is followed, aimed at analyzing and describing patterns in Spanish work-related phraseology. Results: The findings reveal a predominance of transitive structures and figurative constructions built around verbs such as to sweat, to break oneself, to earn and to get oneself, all conveying semantic nuances of effort, hardship, or necessity. Common metaphors include portrayals of work as a burden, a battle, or a form of punishment, with an implicit evaluative component. Conclusions: Spanish work-related phraseology conveys a view of labor tied to physical strain and the struggle for survival. This perspective is encoded in expressions that cognitively frame the concept of work and reinforce a particular ideology surrounding it.